Between the Local and the Global. I International Siberian Philological Forum (October 24–28, 2016, Russia, Krasnoyarsk) (Proceedings of Southern Federal University. Philology, 2017)
CHRONICLES Kotelevskaya V.(October 24–28, 2016, Russia, Krasnoyarsk)